Social Reality of Employment in Bengkulu Province: Policy Analysis of Programs, Obstacles, and Challenges - Reza Oktaviani; Ahnaf; Santi Nugraha; Diah Nadiatul Jannah (PT. Gudang Pustaka Cendekia, 2026)
Employment is an activity undertaken by individuals to earn income in order to sustain a decent standard of living. Employment relationships are established through agreements between employers and workers, and such agreements should ensure decent work conditions. However, in reality, there is insufficient government supervision in ensuring the fulfillment of workers’ rights in accordance with Law No. 13 of 2003. The distribution of rights for female workers is also not optimally implemented. In addition, workforce skills remain a concern, as many workers only possess primary to junior secondary education. Furthermore, freelance work has become increasingly popular due to its flexibility in time and location. Therefore, solutions are needed to address employment issues in Bengkulu Province. Data collection in this study was conducted through interviews with the Bengkulu Provincial Manpower Office. Data analysis employed a qualitative approach. The findings indicate that many workers are engaged in seasonal sectors with unstable income. The Bengkulu Provincial Manpower Office has implemented programs such as job fairs, vocational training and education, and occupational health and safety socialization. Generation Z is perceived as less loyal and tends to frequently change jobs, showing a strong preference for freelance work due to its flexibility. Policy development is needed to provide legal protection for workers. Recommended actions include stricter enforcement against companies violating labor rights, particularly those committing violence against female workers, conducting awareness programs in collaboration with the Ministry of Women’s Empowerment and Child Protection and labor protection institutions, and optimizing integrated reporting systems to accelerate the resolution of such cases.